Literature Review Sensory Marketing Analysis: Theoretical Foundations, Practical Applications, and Their Impact on Consumer Behavior - Richadinata, Kadek Riyan Putra; Wardana, I Made; Ekawati, Ni Wayan; Aksari, Ni Made Asti (Global Health Science Group, 2024)
Sensory marketing has emerged as an important strategy for businesses aiming to create lasting impressions and emotional connections with consumers. This study explores the theoretical foundations, practical applications, and impact of sensory marketing on consumer behavior. Sensory stimuli—such as visual, auditory, olfactory, gustatory, and tactile elements—play a critical role in shaping consumer perceptions and behaviors. The study suggests that sensory marketing not only influences immediate purchase decisions but also fosters long-term brand loyalty by creating memorable experiences. This study systematically reviews the current literature to evaluate the effectiveness of sensory marketing across multiple contexts, including physical retail environments, e-commerce, and the luxury goods market. data search with the keywords typed to search for articles are: